Greatest Responsibility of Human Being In the light of the Holy Qur’an and Ḥadith - Lubis , Tonang B. Hasan (Advances in Social Sciences Research Journal, 2019)
This important issue is related to all divine religions, especially the Islamic religion, because it is related to Adam and his descendants in the world. We depended on the critical descriptive approach, so we dealt with the religious texts of Qurʼan and Hadith by explaining them, so that we can reach a fruitful result that benefits everyone. We also avoided the differences between the clergy in each religion on this subject. First, we mentioned the definition of this great responsibility, and the truth of this responsibility with all its dimensions, especially with regard to harnessing the universe because God Almighty ridiculed to man all that is in the heavens and the earth to occupy this great honor that he is the most honorable creature. Then we dealt with the divine guidance by sending the prophets and messengers, and the opening of the door of repentance, and forgiveness for the sins, mistakes and forgetfulness. As well as, we mentioned also the role of Satan in the human behavior, and how not to ignore this great responsibility and remember it, and control the evil soul by remembering God by His qualities, and reflect on the verses of the universe, especially what is mentioned in the Qurʼan and the prophetic Hadith. Finally, it emerged from the results of the study that there is nothing in our world fit to carry this responsibility, but the great man who is bigger and stronger than the devils, even from angels in terms of carrying this responsibility.